Atraumatic Splenic Rupture in a Patient on Apixaban and Dual Antiplatelet Therapy - Piruthiviraj Natarajan MD; Sudhagar Thangarasu MD, FACP; Lela Ruck MD; Paul Estrada MD; Mahesh Gajendran MD, MPH; Gowri Renganathan MD; Bharat Ved Prakash MD; Olufemi Aduroja MD, MPH (Journal of Investigative Medicine High Impact Case Reports, 2021)
Splenic rupture due to any cause is a life-threatening complication and commonly attributed to trauma. Atraumatic splenic rupture is very rarely reported, and the incidence is currently unknown. Anticoagulants and dual anti-platelet medication can increase the chances of a splenic rupture. Surgical removal of the spleen may be warranted to prevent a life-threatening bleeding. Early identification and intervention are required for most patients as only a few qualify for medical management.